Study on Summer Thermal Comfort and Its Influencing Factors in the Qingshan Lake Greenway - Yao, Yining; Xu, Wenhui (International Journal of Natural Resources and Environmental Studies, 2026)
As urbanization accelerates, the urban heat island (UHI) effect increasingly impacts the ecological environment and residents’ thermal comfort. Greenways, functioning as multifunctional linear green open spaces, play a vital role in improving the urban thermal environment. However, the mechanisms by which internal spatial characteristics affect microclimate and thermal comfort remain unclear. Taking 10 spatial types within the Qingshan Lake Greenway as a case study, this research utilized measured microclimatic data to calculate the Physiological Equivalent Temperature (PET), revealing the spatiotemporal variations of thermal comfort within the greenway. Concurrently, an indicator system for greenway spatial characteristics was established. Correlation analysis and stepwise regression models were applied to uncover the impact mechanisms of various spatial features on the microclimate and thermal comfort. The results indicate that: (1) Within the Qingshan Lake Greenway, the degree of shading exerts a more substantial influence on human thermal comfort than water body area. The comprehensive thermal comfort across different periods ranked as follows: 17:30–18:30 > 09:30–10:30 > 16:30–17:30 > 10:30–11:30. (2) Greenway spatial characteristics significantly influence air temperature, relative humidity, and globe temperature, whereas the effects on wind speed and solar radiation are comparatively minor. (3) The green space ratio, green view index (GVI), permeable surface ratio, spatial coverage, spatial enclosure, and sky view factor (SVF) significantly affect human thermal comfort. The stepwise regression equation linking average PET to these influencing factors is expressed as: PETmean = 40.261 + 1.157 * green space ratio – 1.331 * subsurface permeability rate – 5.390 * coverage degree. These findings provide crucial guidance for optimizing the internal spaces of suburban greenways and enhancing the thermal comfort of human settlements.